Effecting Carrying Capacity of Parks in Korba City: Using Cifuentes Method - Jui Giri; Vandana Agrawal; Swasti Sthapak (Journal of Advanced Zoology, 2023)
In the process of rapid urbanization, the need for green open spaces is increasing, predominantly that of parks. Parks play a vital role in the social, economic, and physical well-being of city dwellers. Park visitors often prefer to visit parks, which have good potential to accommodate the optimal number of visitors without compromising the quality of experience. Due to the lack of understanding of parks and visitors’ requirements, parks are either under-utilised or over-utilized. The optimal visitors carrying capacity is an important parameter to assess the optimal number of visitors an Urban park can accommodate in a given time. This study presents a method to calculate the optimal carrying capacity of visitors. For this purpose, a conventional three-level procedure of visitor carrying capacity for parks was considered in Korba City. In this regard, the physical, real and effective carrying capacity was estimated using “the Cifuentes method”. For this study, three parks from Korba City (C.G., India) were selected that are Silver jubilee park, Smriti nagar park and Vivekanand Udyan. The finding of research indicates that the mentioned three parks were working below the limit of carrying capacity, which means the facilities are underutilised. The outcome signifies may serve as a tool for the future planning of parks as well as other type of ecological environment such as national parks and zoo used for recreational activities. Hence, landscape architects, city planners and policymakers can work in the direction to derive significant information about the parks and park visitors for the optimal utilisation of the park